Overviewing the Incorporation of Environmental Education in Teaching and Learning by Teachers - Sikhosana, Lettah (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study overviews the incorporation of environmental education within the senior phase curriculum in three selected primary schools in a district situated in the Mpumalanga province of South Africa. By examining the implementation process, pedagogical approaches, and perceived outcomes, this study aims to provide comprehensive insights into the effectiveness of incorporating environmental education at this educational level. The study involved three purposively selected grade 7 teachers as participants. Through a multiple case study design, the study explores the alignment of environmental education with broader educational goals, the challenges encountered, and the strategies teachers employ. Qualitative data were collected through interviews and classroom observations. The study demonstrated that teachers encountered fundamental challenges incorporating environmental education in the senior phase. These challenges include inadequate resources, time constraints within an already demanding curriculum, teacher preparedness, and the need for innovative assessment methods. The findings contribute to the localized context and offer valuable implications for enhancing environmental education incorporation in senior phases across diverse educational settings.